Efeitos do tratamento com sildenafil sobre a função vasoconstritora na hipertensão experimental - Fahning, Bernah Mathias (2014)
Cardiovascular diseases account for the majority of pre-mature deaths in thee world. Hypertension is a disease and a risk factor for CVD, and is considered one of the major challenges in public health. Hypertension is a multifactorial condition characterized by high and sustained levels of blood pressure often associated with functional and/or structural changes in target organs. The renovascular hypertension is defined as hypertension due to renal ischemia, usually caused by a partial or complete obstructive lesion of one or both renal arteries. The first experimental studies dating back to 1934 by Goldblatt and colleagues. The model was initially used in dogs which was partially blocked one of the renal arteries in order to study their effects. It was later adapted to rats and mice and such a model used worldwide was known for 2K1C. The mechanism involved in the development and maintenance of 2K1C hypertension is the continuous activation of the renin-angiotensin-system. Previous studies have shown that this model develops endothelial dysfunction and increased oxidative stress, which damages your vascular function. Within this context, sildenafil appears as an alternative treatment, due to the fact that an inhibitor of PDE5 enzyme, increasing the supply of cGMP and therefore the NO. In addition, other studies have shown that sildenafil decreases the activity of NADPH oxidase is a key enzyme production of ROS. The objective of this study was to evaluate the effects of sildenafil on the contractile function, oxidative stress and production of angiotensin fractions. Male mice were C57BL/6 mice with approximately 23 grams. The animals were divided into three groups: Sham, 2K1C 2K1C and treated with sildenafil (40 mg/kg/day). Treatment started 14 days after the induction of hypertension. 28 days after implantation of the dummy clip or surgery some animals were cannulated for blood pressure measurement and cardíacada frequency, other animals were anesthetized, LVM was cannulated and isolated for evaluation of contractile function through the construction of dose-response curves to norepinephrine (NOR). The kidneys were removed and some were stored in liquid nitrogen for determination of thiobarbituric acid (TBARS) which reflects lipid peroxidation consequence of oxidative stress present in this model of hypertension. The plasma was stored for checking the levels of angiotensin fractions. The maximal response (Rmax) and the negative logarithm of drug concentration which caused halfmaximal response (pEC 50) was calculated. Results of pharmacological maneuvers were expressed as the difference in area under the curve (ΔAUC). Results were expressed as mean ± SEM. Statistical comparisons of dose-response curves were made by 2-way ANOVA followed by post hoc Tukey test. Comparisons of Rmax and pEC50, biological parameters, hemodynamic measurements, angiotensin dosage and TBARS were made by ANOVA 1 way followed by post hoc Bonferroni. A value of p <0.05 and p <0.01 were considered statistically significant. The 2K1C animals showed an increase in mean arterial pressure and heart rate (127.9 ± 3.8 and 514.2 ± 7.4, respectively) when compared to the sham group (105.2 ± 2.4 and 441 ± 9.7) and treatment with sildenafil decreased MAP and HR (114.7 ± 2.4 and 471.4 ± 12) compared to 2K1C animals. The fractions of plasma angiotensin I and II did not show significant changes between the groups and the fraction of angiotensin-(1-7) proved to be higher in animals treated with sildenafil compared to 2K1C and sham groups (146 ± 13.3 vs. 102 ± 10.4 and 100, respectively). Likewise the TBARS 2K1C animals show increased if compared to the sham group being restored after treatment with sildenafil (101.5 ± 9.1 vs 63.7 ± 7.0 vs. 64.4 ± 12.5, respectively). The 2K1C animals showed marked hyperresponsiveness when compared to the sham NOR (Rmax 162 ± 14 vs. 118 ± 12, respectively) and the treatment with sildenafil was able to revert the displayed hyperreactivity (116 ± 9). The ΔAUC after removal of endothelium demonstrates that the endothelial function is impaired in 2K1C animals compared to sham (86 ± 7 vs 201 ± 27, respectively), while treatment with sildenafil provides an improvement in this function (134 ± 13). The ΔAUC before and after the addition of apocynin (blocker of NADPH oxidase) shows that the increased contractility 2K1C animals is associated with increased oxidative stress when compared to Sham (101 ± 16 vs 15 ± 6, respectively) and sildenafil deletes this increase in NADPH oxidase ativadade (4 ± 2). Thus it can be concluded that the treatment with sildenafil improves vascular function in experimental hypertension. The mechanisms involved involve increased levels of Ang-(1-7), decreased oxidative stress and improved endothelial function, reflecting also on the improvement of MAP and HR.